An Existence Result for a Class of Coupled Polyharmonic Systems (Contemporary Mathematics, 2021)
This work deals with the existence of positive continuous solutions for a nonlinear coupled polyharmonic system. Our analysis is based on some potential theory tools, properties of functions in the Kato class Km, n and the Schauder fixed point theorem.
Keywords: positive solutions, Kato class, Green function, nonlinear coupled polyharmonic system, Schauder's fixed point theorem